The Human Resource Policy of Tourism in Indonesia - Rhama, Bhayu (Opción, 1970)
Human Resource (HR), especially in tourism, is the driving force that provides services and determines tourists’ satisfaction. However, several studies show that tourism in Indonesia has weaknesses in this sector. Therefore, this study analyses HR policies of tourism in Indonesia since the establishment of Law No. 10 of 2009 on Tourism using a framework of economic development and stakeholder theory that has a focus on plurality, legitimacy, interdependence and transformation. The data used are secondary data collected from government databases and supported by several previous studies. The results showed that HR policies in Indonesia tourism can be seen only in three regulations namely the National Tourism Master Plan/ Rencana Induk Pembangunan Pariwisata Nasional (Ripparnas), the National Medium-Term Development Plan / Rencana Pembangunan Jangka Menengah Nasional (RPJMN), and the Sustainable Tourism Destination Guidelines / Pedoman Destinasi Pariwisata Berkelanjutan (PDPB). The results also showed that plurality is most visible in PDPB, unfortunately, interdependence is less visible in HR policies due to weak relations with academics. Besides, Ripparnas and RPJMN also deliver less influence on HR development due to weak legitimacy. Conversely, the process of transformation on all parties was reached even before the policy was established because of the needs caused by tourism activities. However, HR policies in tourism allow a more structured, comprehensive and beneficial transformation for all parties. The RPJMN 2020-2024 provides a promising tourism development because it exclusively focuses on tourism human resources and has the potential to achieve the plurality, legitimacy, interdependence and expected transformation.